Artificial Artificial habitat design (Dogania subplana) the area Turtle Learning Center (TLC) Universitas Bengkulu - Adriataspen, Milzen; Karyadi, Bhakti; Parlindungan, Deni; Ruyani , Aceng; Nursa’adah, Euis (Universitas Negeri Yogyakarta, 2025)
Malayan soft- shelled Turtle (Dogania subplana) is a species of freshwater softshell turtle that inhabits streams and swamps. This species is considered threatened with extinction and is listed in Appendix III of CITES and as Least Concern by the IUCN. This study aims to design an artificial habitat as a conservation effort and to identify the behavioral adaptations of Dogania subplana. The research method used an ecology-based design. The research subjects were five individuals of D. subplana, consisting of three females and two males. Data collection methods included field observation, literature review, and documentation. Research instruments involved environmental sensors to measure abiotic data. Data analysis was conducted both qualitatively and quantitatively. Qualitative data were analyzed descriptively through systematic and accurate reviews based on field findings and supported with photographic documentation. Quantitative data were analyzed using the average percentage of observed behaviors, presented in graphs, and supported by measured environmental abiotic data. The study results outline the stages of artificial habitat design for D. subplana, which include: location design, area division based on function, addition of supporting biota, fencing, and acclimatization. Observations revealed three behaviors feeding, basking, and aggression which were influenced by environmental temperatures from 26–31°C. D. subplana behaviors were observed only in aquatic areas with sandy and rocky substrates, indicating that such behaviors are strongly influenced by both terrestrial and aquatic environmental conditions. The study concludes that the artificial habitat at the Turtle Learning Center (TLC) of the University of Bengkulu, designed with three zones land, mud, and water effectively supports the natural adaptations and activities of D. subplana, as indicated by their feeding, basking, and aggressive behaviors.